Robert B. Parker's Colorblind : a Jesse Stone novel - Coleman, Reed Farrel, 1956- (The Jesse Stone novels, 2018)
Jesse Stone is back on the job after a stint in rehab, and the road to recovery is immediately made bumpy by a series of disturbing and apparently racially motivated crimes, beginning with the murder of an African American woman. Then, Jesse's own deputy Alisha--the first black woman hired by the Paradise police force--becomes the target of a sophisticated frame-up. As he and his team work tirelessly to unravel the truth, he has to wonder if this is just one part of an even grander plot, one with an end game more destructive than any of them can imagine. At the same time, a mysterious young man named Cole Slayton rolls into town with a chip on his shoulder and a problem with authority--namely, Jesse. Yet, something about the angry twenty-something appeals to Jesse, and he takes Cole under his wing. But there's more to him than meets the eye, and his secrets might change Jesse's life forever.